Probiotic supplementation during pregnancy alters gut microbial networks of pregnant women and infants - Huang, Ting; Li, Zhe; Tye, Kian Deng; Chan, Sze Ngai; Tang, Xiaomei; Luo, Huijuan; Wang, Dongju; Zhou, Juan; Duan, Xia; Xiao, Xiaomin (Frontiers in Microbiology, 2022)
Probiotic supplementation has been becoming popular and widespread, yet we still lack a comprehensive understanding of how probiotic supplementation during pregnancy affects the gut microbial networks of pregnant women and infants. Here, we firstly used network analysis to compare the gut microbiota of pregnant women with and without probiotic supplementation, as well as their infants. In this study, thirty-one pairs of healthy pregnant women and infants were recruited and randomly divided into the probiotic group (15 mother-infant pairs) and the control group (16 mother-infant pairs). Pregnant women in the probiotic group consumed combined probiotics from 32 weeks to delivery. The fecal samples were collected from pregnant women and infants at several time points. The results showed that probiotic supplement does not change the microbial alpha and beta diversity of pregnant women and infants, but significantly alters the intestinal microbial network structure and properties. The total links, average degree, average clustering coefficient, robustness, and the proportion of positive correlations were increased in pregnant women with probiotics administration. In contrast, these indices were decreased in infants in the probiotic group. These results indicated that although pregnant women have more complicated and stable networks after probiotic administration, their infants have less stable networks. Our study expands the understanding of the effects of probiotics on gut microbiota.